Tinjauan Maqoshid Syariah Pada Marketplace B2C di Indonesia (Studi di Halalpedia dan Bhineka) - Kalsum, Umi (Indonesian Journal of Islamic Economics and Business, 2022)
This study aims to review the practice of buying and selling in several marketplaces with the B2C (business to customer) concept in Indonesia based on the maqoshid sharia aspect. The marketplace in question is Halalpedia and Bhinneka. Content analysis on the marketplace is used to describe the object of research, while the normative descriptive method is used to review the maqoshid sharia aspects. The results of the study show that in general the two marketplaces already support the maqoshid sharia aspect, but there are still aspects such as hifzul maal such as the certainty of the originality of goods and the COD system that has not been optimally implemented